Mean performance of newly developed restorer lines of sunflower (Helianthus annuus L.) for different agronomical traits: Mean performance of newly developed restorer lines of sunflower (Helianthus annuus L.) for different agronomical traits - G SANDHYASREE,; A VISHNUVARDHAN REDDY,; V ROJA,; H P MEENA, (Journal of Oilseeds Research, 2020)
The investigation was carried out at ICAR-Indian Institute of Oilseeds Research, Hyderabad. The material for present study consisted of 25 newly developed restorer lines including two checks. The data for agronomic and yield traits was recorded. Four genotypes namely CMS-1010B, RGP-58-P4-S2,RGP-26-P2 and RGP-26-P2-S2were identified as the most promising for yield and yield contributing traits and can be utilized in hybridization program to realize high heterosis for these traits.